Pesquisa em consolidação do fechamento de vazios internos em produtos forjados no aço W.Nr. 1.2738 modificado - Campos, Gustavo Acarine Ferraz de (2018)
During steel ingot solidification, internal voids are expected to be formed in its interior. Such voids, if they stay in the final product after the forging step, will hurt the performance and properties of the final product, and, therefore, they must be eliminated. Aiming voids elimination, forging process parameters must be chosen in a way possible to allow diffusion bonding. So far, there are no standardized tests to analyze the influence of processing variables. Thus, this work aims to develop a test that physically simulates thermomechanical conditions to subsequently realize tests to determine the conditions of strain and temperature so that the diffusion bonding may occur in steels' molds for polymers. The interface region was analyzed through optical microscopy to determinate the effectiveness of the phenomena of healing voids. The ideal process parameters to a satisfactorily bond were found, and it is intended, in a next step, to implement them in a real process.